2018
DOI: 10.1108/mip-11-2017-0272
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of counterfeit clothing and apparel products attributes

Abstract: Purpose The purpose of this paper is to test and validate a modified Stimulus-organism-response (S-O-R) model with the bi-dimensional attitude toward counterfeit apparel products. The study examines the relationship of object and social psychological stimuli with utilitarian and hedonic attitude and intentions to purchase counterfeit apparel products. Design/methodology/approach The authors collected data from 331 systematically selected university students of the age bracket (18–30) years from Punjab, Pakis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 44 publications
8
64
0
Order By: Relevance
“…Further, consumer ASC was found to positively predict SCI (H2, ß = .34). These findings complement previous findings on sustainable consumption (Moon et al, ; Yadav & Pathak, .). This finding implies that an individual's ASC is shaped through the individual's cognitive assessment of the significance of sustainable consumption practices (Chan, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Further, consumer ASC was found to positively predict SCI (H2, ß = .34). These findings complement previous findings on sustainable consumption (Moon et al, ; Yadav & Pathak, .). This finding implies that an individual's ASC is shaped through the individual's cognitive assessment of the significance of sustainable consumption practices (Chan, ).…”
Section: Discussionsupporting
confidence: 91%
“…Young purchasers have versatile thoughts and ability in understanding the significance of green purchasing (Kanchanapibul et al, 2014). Recent studies have found that young educated consumers are more prone to engage in environmental behaviours in emerging economies (Khare, 2015;Yadav & Pathak, 2017), and understanding their consumption behaviour may provide valuable insights as to how their consumption patterns are going to shape up in future (Moon et al, 2018). Understanding students' green consumption is imperative because they constitute an understudied group of the population in environmental research (Chuvieco, Burgui-Burgui, Da Silva, Hussein, & Alkaabi, 2018;Yadav & Pathak, 2017).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research findings suggest that consumers with counterfeit experience have a more positive attitude toward counterfeits than consumers who have little experience (Nia and Zaichkowsky 2000). Counterfeit evaluations of experienced consumers are more positive than less experienced consumers (Penz and Stöttinger 2008;Moon et al 2018). Yoo and Lee (2009) have also presented empirical evidence that past experience of counterfeits and original branded products have a positive influence on purchase intention of counterfeits and originals.…”
Section: H 7dmentioning
confidence: 98%
“…In addition, the United States must influence the demand for illegal and pirated products and educate U.S. consumers to turn away from these products towards legitimate alternatives, in order to "educate consumers on the negative impacts of the counterfeit products not only on consumers but also on the economy as a whole" (Moon, Javaid, Kiran, Awan, & Farooq, 2018).…”
Section: Physical Marketsmentioning
confidence: 99%